Integrating Genomic and Morphological Approaches in Fish Pathology Research: The Case of Turbot (Scophthalmus maximus) Enteromyxosis - Ronza, Paolo; Robledo, Diego; Bermúdez, Roberto; Losada, Ana Paula; Pardo, Belén G.; Martínez, Paulino; Quiroga, María Isabel (Frontiers in Genetics, 2019)
Enteromyxosis, caused by Enteromyxum scophthalmi, is one of the most devastating diseases stemming from myxozoan parasites in turbot (Scophthalmus maximus L.), being a limiting factor for its production. The disease develops as a cachectic syndrome, associated to catarrhal enteritis and leukocytic depletion, with morbidity and mortality rates usually reaching 100%. To date, no effective treatment exists and there are different unknown issues concerning its pathogenesis. The gross and microscopic lesions associated to enteromyxosis have been thoroughly described, and several morphopathological studies have been addressed to elucidate host-parasite interaction. More recently, efforts have been focused on a multidisciplinary approach, combining histopathology and transcriptome analysis, which has provided significant advances in the knowledge of the pathogenesis of this parasitosis. RNA-Seq technology was applied at early and advanced stages of the disease on fishes histologically evaluated and classified based on their lesional degree. In the same way, the transcriptomic data were analyzed in relation to the morphopathological picture and the disease course. In this paper, a comprehensive review of turbot enteromyxosis is addressed, starting from the disease description up to the most novel information extracted by an integrated approach on the infection mechanisms and host response. Also, we discuss the ongoing strategies towards a full understanding of host-pathogen interaction and the identification of suitable biomarkers for early diagnosis and disease management strategies.